Information seeking behaviour of the ulama in relation to their work roles - Saleh, Adam Gambo (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2013)
Information seeking behaviour (ISB) studies is one area in library and information science that has over the years attracted the attention of information professionals, resulting in several studies being carried out with a view to understand why people seek information, how they seek it, and the problems encountered. While an enormous amount of literature has shown that several professional groups' ISB has been studied, an important and influential group of professionals, the Muslim clerics (Ulama) has been totally neglected. Thus, the main objective of the study was to investigate the ISB of the Ulama in relation to preaching, counselling, administration, and leadership roles in Nigeria. The study answered such questions as (1) What are the information needs of the Ulama? (2) What types of information sources and resources do they use? (3) How do they seek information for their preaching, counselling, administrative, and leadership roles? and (4) What are the barriers affecting their information seeking? The study is quantitative and deployed the survey research design. The target population was made up of 973 Ulama dispersed within 27 local government areas of Borno State. Proportional stratified random sampling was used to arrive at the sample size of 284. The study used both questionnaire and interview schedule which were conceived by the researcher and developed in line with the works of Wicks (1997) and Kamba (2010). The questionnaire was also validated by experts and Cronbach reliability test was carried out to determine its internal consistency. Data collected was processed using SPSS and then subjected to both descriptive and inferential statistical procedures. The result of the analyses revealed that the ISB of the Ulama showed some similarities with other clergies as reported in the literature. However, the study also found out that the Ulama consider their roles as sacred, hence used the Qur'an and Hadith as ultimate resources to perform their roles. The study also found out that the Ulama preferred and relied on printed resources from their personal collection or that of colleagues. While they are aware of the Internet as a source of information, they seldom access and use it. The study has found out that apart from the environmental, educational, technological, political and economic barriers affecting the ISB of the Ulama, the Islamic tradition of reading rooted in print, the sacred nature of their roles and the perception of technology as 'western', coupled with lack of skills and resources to access and use the Internet, were perhaps, the factors that attributed to the difference in the ISB of the Ulama. The study has also established significant relationships between demographic factors and information sources consulted, and search strategies adopted. The study also proofed that the Leckie et al.'s (1996) Professional Information Searching Strategy Model can be suitably adapted and applied to all professions and in any environment. As a pioneer research in the ISB of the Ulama, the study has not only bridged the literature gap existing in ISB especially within the religious context, and an invaluable source of information for librarians, database developers and system analyst, but also provided new grounds for research in the area of information seeking, needs, use, and ICT in the Muslim world. Finally, the study made recommendations to information professionals, the council of Ulama, government agencies, and Borno State government in particular, and the government of Nigeria in general.